BiOCl Decorated NaNbO3 Nanocubes: A Novel p-n Heterojunction Photocatalyst With Improved Activity for Ofloxacin Degradation - Xu, Jingjing; Feng, Bingbing; Wang, Ying; Qi, Yadi; Niu, Junfeng; Chen, Mindong (Frontiers in Chemistry, 2018)
BiOCl/NaNbO3 p-n heterojunction photocatalysts with significantly improved photocatalytic performance were fabricated by a facile in-situ growth method. The obtained BiOCl/NaNbO3 samples were characterized by ultraviolet diffuse reflectance spectroscopy (DRS), scanning electron microscopy (SEM), X-ray diffraction (XRD), photocurrent (PC) and photoluminescence spectroscopy (PL). The photocatalytic activity of the BiOCl/NaNbO3 samples was investigated by the degradation of a typical antibiotic Ofloxacin (OFX). The experimental results showed that BiOCl/NaNbO3 composites exhibited much higher photocatalytic activity compared to pure NaNbO3 and BiOCl. The degradation percent of OFX reached 90% within 60 minutes, and the apparent rate constant was about 8 times as that of pure NaNbO3 and BiOCl. The improved activity can be attributed to the formation of p-n junction between NaNbO3 and BiOCl. The formed p-n junction facilitated the separation of photogenerated holes and electrons, thereby enhancing photocatalytic activity. In addition, the composite photocatalyst showed satisfactory stability for the degradation of OFX. Due to the simple synthesis process, high photocatalytic activity, and the good recyclability of these composite photocatalysts, the results of this study woule provide a good example for the rational design of other highly efficient heterojunction photocatalytic materials.